KAJIAN INDEKS MASSA TUBUH (IMT) TERHADAP TEKANAN DARAH PADA PERAWAT DI RUMAH SAKIT BAPTIS KEDIRI - Richard, Selvia David; Bungawati, Dahlia; Pratama, Kayetanus Aldy (Jurnal Penelitian STIKES Kediri, 2011)
abstract backgorund : BMI (Body Mass Index) is a measure that helps determine whether a person at risk of contracting diseases associated with weight. Being overweight can increase the risk for cardiovascular disease because of the greater a person's body mass, the more blood is needed to supply oxygen and food into body tissues, causing the rise of blood pressure. The relative risk for hypertension in people with BMI > 25 is five times higher than someone whose weight is normal. The objective of this research is to know the relationship of Body Mass Index (BMI) with blood pressure on nurse at Kediri Baptist Hospital. Method : The design used in this study was cross sectional. The population was all of Nurses at Kediri Baptist Hospital. It was taken by Simple Random Sampling technique so obtained the 89 nurses of respondents in accordance with inclusion criteria. The Independent variable was Body Mass Index (BMI) and the dependent variable was blood pressure. Data were collected by direct measurement. Processing data used Spearman's Rho statistics test with significance level α = 0.05. Conclusion : The result of the research showed that nurses who had a BMI : skinny as much as 4.50%, normal as much as 78.65%, and fat as much as 16.85%. Meanwhile the optimal categories of systolic blood pressure as much as 62.92%, normal as much as 34.83%, and hypertension as much as 2.25%. For optimal category diastolic blood pressure as much as 56.18%, normal as much as 40.45%, and hypertension as much as 3.37%. Key words : Body Mass index (BMI), Blood pressure.